ANALISIS KINERJA GURU YANG TELAH BERSERTIFIKASI PADA JENJANG MI/SD - Nurfitria Maulana Putri; Maknun, Lu'luil (Universitas Islam Malang, 2024)
The purpose of writing this article is to describe the performance analysis of teachers who have been certified at the MI/SD level. The approach in this research is a qualitative approach. From several studies, it is stated that teachers who have passed certification become professional and have better performance than teachers who have not followed certification. However, there are still some certified teachers who are still lacking in improving their performance. The conclusion generated based on the discussion is that the competence and performance of teachers who are already good and professional on average are owned by certified teachers. There are still some teachers who have been certified but their performance has not been maximized but the number is only small. Thus, teacher certification has a positive impact on improving teacher competence and performance. Keywords: Teacher Performance, Certification, Elementary Education.